Technical Note: Notes on Determining Required Connector Strength in Built-up Compression Members - Geschwindner, Louis F. (Engineering Journal, 2020)
Connections between individual components of a built-up compression member carry no force when the member is perfectly straight in the unbuckled configuration under load. Yet AISC Specification Section E6.1 (AISC, 2016) requires that the end connection of these built-up members be welded or connected by means of pretensioned bolts with Class A or B faying surfaces. Nothing is provided in the AISC Specification or Commentary to help the designer determine the required strength of these connectors. This paper suggests one way of determining these required strengths and provides two LRFD examples. Other assumptions may be used to derive different, but equally acceptable, required strengths.